The Relationship Between 3 Months Of Injecting KB Use With 3 Months Of Injecting Kb Acceptors' Weight Gain At Mahdalena Pane Clinic - Arva Rochmawati; Nurdiana Manurung Manurung (Science Midwifery, 2019)
Women are very afraid of gaining weight, because in addition to making their physical appearance unattractive, being overweight can have serious consequences for health. This study aims to determine the relationship between duration of use of 3 months injectable contraception and weight gain of 3 months injectable family planning acceptors at the Mahdalena Pane Clinic. This research method uses analytic observational method with a cross-sectional approach.The population in this study were 105 acceptors of 3-month injections in Mahdalena Pane. sampling by accidental sampling, namely 35 acceptors of 3-month injections at Mahdalena Pane in 2019.The results of the Chi-Square test obtained a value of = 0.000, this means that the p-value is smaller than (0.05), which means that there is a relationship between the duration of the use of injectable contraception for 3 months and the increase in body weight of the 3 month injection KB acceptor. It is hoped that health workers, especially midwives, will provide counseling about acceptors of 3-month injection KB at the Mahdalena Pane Clinic in 2019 to increase knowledge about 3-month injection KB.